Independent Corporate Governance Organ Busyness, Earnings Quality, And Market Mispricing: Evidence From Indonesia - Oktavia; Febriani Cristina Susianti Magdalena; Hartoni; Eva Oktavini; Krisnawati Tarigan (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2023)
This research aims to give empirical evidence of the impact of independent corporate governance organ's busyness on earnings quality and market mispricing. This research utilized a sample of non-financial firms. It investigated the effect of independent corporate governance organ's busyness on earnings management and earnings persistence using random-effect panel data regression. Furthermore, the Mishkin Test was used to investigate market mispricing. The results showed that the busyness of independent commissioners and independent audit committees had a positive effect on increasing the magnitude of earnings management and a negative impact on the persistence of the accrual component but did not cause market confusion in assessing the company's earnings components. Furthermore, it was discovered that the degree of independent director's business did not influence the magnitude of earnings management. Instead, it resulted in poor persistence of the accrual component and market uncertainty in assessing earnings components.